INNOVATIVE HORIZONS: CREATIVE MANAGEMENT AS A KEY TO TRANSFORMATION OF OIL AND GAS ENTERPRISES - Mykytiuk, Nataliia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article examines theoretical-methodological and applied aspects of implementing creative management as a key tool for transforming oil and gas enterprises of Ukraine in the context of global energy changes. The relevance of transitioning from traditional to innovative management models capable of ensuring adaptability and competitiveness of industry enterprises in the long term is substantiated. Based on the analysis of scientific sources, the essence and features of creative management in the context of the specifics of the oil and gas industry are clarified. Problems of managing innovative development of oil and gas enterprises are identified, including: lack of long-term development strategies, low level of investment in research, insufficient digitalization of business processes, inflexible organizational structures. Key barriers to implementing creative management (cultural, organizational, competency-based, resource, systemic) are identified and ways to overcome them are proposed. A conceptual model for transforming oil and gas enterprises based on creative management principles is developed, covering five interconnected stages: strategic reorientation, organizational transformation, development of innovation culture, technological modernization, and ecosystem integration. Based on systematic analysis of industry specifics, a set of practical recommendations for gradual implementation of creative management principles is formed, aimed at creating adaptive organizational structures, developing innovation culture, and diversifying business models of oil and gas enterprises. It is proven that creative management under current conditions is a strategic imperative for oil and gas enterprises, determining their ability to adapt to the challenges of energy transition and utilize new opportunities in the era of global economy decarbonization.